Copper associates with differential methylation in placentae from two US birth cohorts. Issue 3 (3rd March 2020) - Kennedy, Elizabeth; Everson, Todd M.; Punshon, Tracy; Jackson, Brian P.; Hao, Ke; Lambertini, Luca; Chen, Jia; Karagas, Margaret R.; Marsit, Carmen J.
ABSTRACT: Copper is an essential trace nutrient and an enzymatic cofactor necessary for diverse physiological and biological processes. Copper metabolism is uniquely controlled in the placenta and changes to copper metabolism have been linked with adverse birth outcomes. We investigated associations between patterns of DNA methylation (DNAm; measured at >485 k CpG sites) and copper concentration measured from placentae in two independent mother-infant cohorts: the New Hampshire Birth Cohort Study (NHBCS, n = 306) and the Rhode Island Child Health Study (RICHS, n = 141). We identified nine copper-associated differentially methylated regions (DMRs; adjusted P < 0.05) and 15 suggestive CpGs (raw P < 1e-5). One of the most robust variably methylated CpGs associated with the expression of the antioxidant, GSTP1. Our most robust DMR negatively associates with the expression of the zinc-finger gene, ZNF197 (FDR = 4.5e-11). Genes co-expressed with ZNF197, a transcription factor, are enriched for genes that associate with birth weight in RICHS (OR = 2.9, P = 2.6e-6, N = 194), genes that are near a ZNF197 consensus binding motif (OR = 1.34, P = 0.01, N = 194), and for those classified in GO biological processes growth hormone secretion (P = 3.4e-4), multicellular organism growth (P = 3.8e-4), and molecular functions related to lipid biosynthesis (P = 1.9e-4). Further, putative transcriptional targets for ZNF197 include genes involved in copper metabolism and placentation. Our results suggest that copper metabolism is tied to DNAm in the placenta and that copper-associated patterns in DNAm may mediate normal placentation and foetal development.